A 3D distributed circuit-electrochemical model for the inner inhomogeneity of lithium-ion battery. (1st February 2023) - Liu, Yang; Zhang, Caiping; Jiang, Jiuchun; Zhang, Linjing; Zhang, Weige; Lao, Li; Yang, Shichun
Abstract: Performance degradation and operational safety are vital issues for lithium-ion batteries. After summarizing each battery failure accident, it is found that local defects caused by the inconsistency within the battery are one of the critical reasons for battery failure. To study the influence of the internal inconsistency of the battery on its safety performance, a 3D distributed circuit and electrochemical coupling model that can reflect the internal structure of the battery are established. Moreover, the model's solid-phase potential and liquid-phase lithium ion concentration are corrected to improve the simulation accuracy. The RMSE of the model is less than 10 mV under 1.0 C constant current charging condition and dynamic discharge condition. Based on the proposed distributed model, this paper investigates the influence of the cell size, tab position, and other structural parameters on the internal inconsistency of the cell. And the phenomenon of "current reversal" and the possible local lithium deposition away from the tab position is discovered. The model's correctness and efficacy in simulating internal inconsistencies are further illustrated by reproducing the local lithium deposition of a homemade LFP cell and a commercial NCM cell by controlling the charging current. Highlights: A 3D model that reflects the internal structure of the cell was established. The model's solid-phase potential and liquid-phase diffusion are modified. The "current reversal" and lithium deposition occur far from the tabs. The local lithium deposition caused by the cell's structural parameters is analyzed. The established model can be used to simulate the internal inconsistency of the cell.